Perkembangan Asuransi Syariah di Indonesia - Umi Kholilah; Rizqi Salamah; Cintia Salsabila; Riski Nilam Sari; Ria Anisatus Solihah; Muhammad Taufiq Abadi (CV. ALIM'SPUBLISHING, 2024)
The purpose of this research is to explain the history, duties, and potential development of Sharia Insurance in Indonesia. In this research, the author uses a qualitative approach with descriptive analysis type of research. This research uses a literature study method or library research sourced from books and journals that are in accordance with the topic and focus of the research. The results of the literature review in this study concluded that sharia insurance is a way to deal with risks and calamities in life, such as death, accidents, illness, and old age. Its main purpose is to provide financial protection, manage risk, apply sharia principles, and empower the community. Islamic insurance products include various forms of protection, such as health insurance, children's education, retirement preparation, and investment.